2005
DOI: 10.1051/forest:2005011
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and morphological responses of dormant and growing Norway spruce container seedlings to drought after planting

Abstract: -Survival, root egress, height growth, xylem water potential, and chlorophyll fluorescence of dormant and growing Norway spruce (Picea abies (L.) Karst.) container seedlings exposed to postplanting drought periods (1, 2, 3 and 4 weeks) in the field were studied. Growth stages were created by terminating overwinter frozen storage 5 weeks (growing) or 5 days (dormant) before planting. Without postplanting drought, root egress of growing seedlings during the 6-week study period was twice that of dormant seedlings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 28 publications
3
23
1
Order By: Relevance
“…temperature, moisture, pathogenic fungi, or light are important factors for Norway spruce (Picea abies (L.) Karst.) seedling development in natural forests [5,14,34]. It has recently been shown that the recruitment of a new spruce generation strongly depends on the quality of the seedbed [14,15,46].…”
Section: Introductionmentioning
confidence: 99%
“…temperature, moisture, pathogenic fungi, or light are important factors for Norway spruce (Picea abies (L.) Karst.) seedling development in natural forests [5,14,34]. It has recently been shown that the recruitment of a new spruce generation strongly depends on the quality of the seedbed [14,15,46].…”
Section: Introductionmentioning
confidence: 99%
“…The plants were taken out of their containers, making every effort to keep their root balls intact. White pre-existing roots (usually less than 5 and shorter than 2 cm long) grown out from each ball were cut [23,56]. It was previously ascertained, using the plants harvested for the dry weight measurements, that there were not white roots inside the root ball at this time.…”
Section: Root Egress From the Root Ballmentioning
confidence: 99%
“…The risk of autumn frost damage can be studied in field experiments by varying the date of storage termination of the planting stock (Ericsson et al 1983, Raulo et al 1994, Luoranen et al 2005. As this experimental design simulates real-life practice, the method produces reliable results.…”
Section: Introductionmentioning
confidence: 99%
“…One traditional way to overcome this problem has been to plant part of the seedlings in the autumn, after they have attained dormancy (Antola and Lehto 1969). More recently, plantings with actively growing seedlings have also produced promising results (Revel et al 1990, Grossnickle and Folk 2003, Luoranen et al 2005, 2006.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation